PERAN MOTIVASI KEPALA SEKOLAH DALAM MENINGKATKAN KINERJA GURU DAN PRESTASI SISWA - Ratna Kusuma Dewi; Noor Miyono (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to analyze the role of motivation provided by the principal in improving teacher performance and student learning achievement at SD Negeri 01 Dororejo. The principal plays a crucial role as a leader in creating a conducive school environment for the teaching and learning process. Through an effective motivational approach, the principal can influence the quality of teacher performance, which ultimately has a positive impact on students academic achievements. This research employs a qualitative approach with data collection techniques including interviews, observations, and documentation at the specific school. The findings indicate that effective motivation from the principal, whether through rewards, good interpersonal communication, or professional support, significantly enhances teacher performance. This improvement contributes significantly to the increase in students learning achievement. The conclusion of this study underscores that the motivation provided by the principal is a key factor in fostering a successful, progressive, and results-oriented educational ecosystem.